The Florida Sleeve Procedure Is Durable and Improves Aortic Valve Function - Aalaei-Andabili, Seyed Hossein; Martin, Tomas D.; Hess, Philip J.; Karimi, Ashkan; Bavry, Anthony A.; Arnaoutakis, George J.; Beaver, Thomas M. (AORTA, 2019)
Background The Florida (FL) Sleeve procedure was introduced as a simplified approach for valve-sparing correction of functional Type I aortic insufficiency (AI) associated with aortic root aneurysms. In this study, short- and long-term outcomes after the FL Sleeve procedure were investigated.Methods From May 2002 to January 2016, 177 patients underwent the FL Sleeve procedure. Left ventricular end-diastolic diameter (LVEDD), left ventricular end-systolic diameter, left ventricular ejection fraction, and degree of AI (none = 0, minimal = 1, mild = 2, moderate = 3, severe = 4) were evaluated by echocardiography.Results Mean ± standard deviation of age was 49.41 ± 15.37 years. Survival rate was 98% at 1 year, 97% at 5 years, and 93% at 8 years. Freedom from reoperation was 99% at 1 year and 98% at 2 to 8 years. Three patients (1.69%) died during hospitalization. Three patients (1.69%) developed periprocedural stroke. Postoperative follow-up echocardiography was available in 140 patients at 30 days, and 31 patients at 5 years. AI grade significantly improved from baseline at 30 days (2.18 ± 1.26 vs. 1.1 ± 0.93, p < 0.001) and at 5 years (2.0 ± 1.23 vs. 1.45 ± 0.88, p = 0.04). Preoperative mean LVEDD significantly decreased from 52.20 ± 6.73 to 46.87 ± 8.40 (p < 0.001) at 30 days, and from 53.22 ± 7.07 to 46.61 ± 10.51 (p = 0.01) at 5 years.Conclusions The FL Sleeve procedure is a safe, effective, and durable treatment of aortic root aneurysm and Type I AI. Long-term survival and freedom from reoperation rates are encouraging.
Keywords: Florida Sleeve; safety; aortic insufficiency; freedom from reoperation